Circulating perturbation of phosphatidylcholine (PC) and phosphatidylethanolamine (PE) is associated to cardiac remodeling and NLRP3 inflammasome in cardiovascular patients with insulin resistance risk - Vianello, Elena; Ambrogi, Federico; Kalousová, Marta; Badalyan, Julietta; Dozio, Elena; Tacchini, Lorenza; Schmitz, Gerd; Zima, Tomáš; Tsongalis, Gregory J; Corsi-Romanelli, Massimiliano M (Experimental and molecular pathology, 2024)
Lipidome perturbation occurring during meta-inflammation is associated to left ventricle (LV) remodeling though the activation of the NLRP3 inflammasome, a key regulator of chronic inflammation in obesity-related disorders. Little is known about phosphatidylcholine (PC) and phosphatidylethanolamine (PE) as DAMP-induced NLRP3 inflammasome. Our study is aimed to evaluate if a systemic reduction of PC/PE molar ratio can affect NLRP3 plasma levels in cardiovascular disease (CVD) patients with insulin resistance (IR) risk. Forty patients from IRCCS Policlinico San Donato were enrolled, and their blood samples were drawn before heart surgery. LV geometry measurements were evaluated by echocardiography and clinical data associated to IR risk were collected. PC and PE were quantified by ESI-MS/MS. Circulating NLRP3 was quantified by an ELISA assay. Our results have shown that CVD patients with IR risk presented systemic lipid impairment of PC and PE species and their ratio in plasma was inversely associated to NLRP3 levels. Interestingly, CVD patients with IR risk presented LV changes directly associated to increased levels of NLRP3 and a decrease in PC/PE ratio in plasma, highlighting the systemic effect of meta-inflammation in cardiac response. In summary, PC and PE can be considered bioactive mediators associated to both the NLRP3 and LV changes in CVD patients with IR risk.
Keywords: Cardiovascular Diseases; senioři; fosfatidylcholiny; Male; Female; protein NLRP3; Middle Aged; Aged; fosfatidylethanolaminy; inzulinová rezistence; Inflammasomes; inflamasomy; Phosphatidylethanolamines; mužské pohlaví; Insulin Resistance; ženské pohlaví; lidé středního věku; kardiovaskulární nemoci; remodelace komor; Phosphatidylcholines; NLR Family, Pyrin Domain-Containing 3 Protein; Ventricular Remodeling; lidé; Humans